Network Structures of Cargo Airlines - An Empirical and a Modelling Approach - Scholz, Aaron Bernhardt (KIT Scientific Publishing, 2012)
The development of efficient air freight networks is an upcoming challenge. The present book approaches this problem for cargo airlines by characterising and classifying their network structures and by developing a model for an airline's strategic network design. The book provides results which are of value for airline professionals (network efficiency analysis), policy makers (policy impact assessment) and researchers (cargo airline network design model).